PENGARUH ATTITUDE TOWARDS ELECTRONIC TAX SYSTEM, PELAYANAN FISKUS, DAN PENERAPAN E-SYSTEM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA JAKARTA SAWAH BESAR DUA - Tri Ameliyaningsih; Lu’lu’ul Jannah (JURNAL INFO ARTHA, 2022)
As a country that is supported by taxes, taxpayer compliance in Indonesia will always be an important discussion in efforts to increase state revenues. This study aims to determine the effect of attitude towards electronic tax system, tax services, and the implementation of e-tax system on individual taxpayer compliance. This research is a type of quantitative research with closed questionnaire data collection techniques to 100 samples of individual taxpayers (WPOP) at KPP Pratama Jakarta Sawah Besar Dua. Tests in this study include validity, reliability, classical assumptions, and multiple regression to be able to determine decisions on the formed hypothesis. The results of this study indicate that attitude towards electronic tax system, tax services, and the implementation of e-tax system have a positive effect on individual taxpayer compliance, either partially or simultaneously. This research was only conducted at KPP Pratama Jakarta Sawah Besar Dua for a certain period of time and did not take into account other variables that could affect individual taxpayer compliance.